DEVELOPMENT OF ONLINE MENTAL HEALTH SUPPORTING GROUP TO REDUCE MENTAL BURDEN DURING COVID-19 PANDEMIC - Annette d’Arqom; Brihastami Sawitri; Zamal Nasution; Dimas Setyanto; Safira Nur Izzah; Ludy Diana Wiradhika; Rakha Achmad Maulana (Universitas Airlangga, 2021)
COVID-19 pandemic affects all aspects of human life, not only health, but also economic, education, and daily activity. The sudden changes caused a mental burden for the majority of people. Moreover, the infodemic might increase the burden. Unfortunately, not all people aware of their mental health, and the negative stigma from the community leads the patient to hesitate for sharing and seeking help. Therefore, an anonymous online supporting group (www.laluibersama.com) is developed to increase awareness of mental health and provided the facility to share and to support users. This site consists of several basic information and articles regarding COVID-19, emphasizes on pharmacotherapy and mental health issues, sharing forum, and mental health calculator based on depression, anxiety, and stress scales (DASS 21). From the evaluation, 53.61% of users choose mental health calculators as the most favorite page, followed by article (29.90%), homepage (12.37%), and sharing page (4.12%). Most of the respondents agree that the mental health calculator is unique and useful, therefore can be used as a screening of mental health problems prior to seeking health professional help. Taken together, mental health needs more attention in this pandemic due to the increasing burden, and the screening of mental health problems and sharing to alleviate the users’ burden can be performed at www.lalui bersama.com.